Agents of Change: The Role of the Peer Education Program in Preventing Adolescent Substance Abuse. Issue 5 (8th August 2019) - Demirezen, Dilek; Karaca, Aysel; Konuk Sener, Dilek; Ankarali, Handan
Abstract: In recent years, peer education programs (PEPs) have put this effect to use in a positive way by providing peers that constitute positive role models for each other. Accordingly, this study was carried out to determine the effect of a PEP on the basic knowledge of adolescents about addiction and on the level of self-efficacy that is needed to avoid substance abuse. The pre-test/post-test design of this semi-experimental study used a sample of 9th year students at three high schools in Duzce, Turkey. Peer educator training (PET) with an interactively structured program was completed within a total of 20 hours. The peer educators (PEs) then implemented the program for three months to groups of 14–16 adolescents. Following program, it was determined that incidence of smoking just for once was significantly decreased and incidences of using ecstasy and non-prescription drugs just for once significantly increased. Significant increases were observed in the attitude scores of self-efficacy scale at three high schools following program. This study showed the effectiveness and applicability of the PEP in preventing substance abuse among high-school adolescents.